Elucidating insights on how care was prioritized, adapted, and missed during and post pandemic - Lianne Jeffs; Jacqueline Limoges; Tracey DasGupta; Lisa Di Prospero; Alexandra Harris; Jane Merkley; Benjamin Rosen; Adebisi Akande; Frances Bruno; Agnes Black; Linda McGillis Hall (PLoS ONE, 2025)
Globally, healthcare systems continue to recover and manage system demands, including our sustained HHR pressures exacerbated by the COVID-19 pandemic. Health system leaders need to understand how healthcare was adapted during the pandemic, what contributed to these changes, and the impact of these changes to inform future efforts. The overarching research questions included: What changes to models of care were made during COVID-19 and post-recovery? What factors contributed to changes in models of care? What was the impact of these changes? An exploratory interpretative descriptive qualitative study was undertaken to describe what HHR strategies and changes to models of care delivery were employed during the COVID-19 pandemic and post-pandemic recovery. An inductive thematic analysis was conducted where an investigation team of research staff identified, coded, and categorized prominent themes that emerged in the interview data. A total of 118 participants from a variety of healthcare professionals and leadership positions across five healthcare organizations in the greater Toronto area in Ontario and 1 setting from British Columbia were interviewed. The following three themes were identified during the inductive analysis: 1) prioritizing care based on system capacity, patient volume and complexity; 2) adapting care by innovating, clustering, and taking shortcuts; and 3) being impacted by prioritized and adapted care. Adapting and prioritizing care resulted in missed or delayed care and moral distress in healthcare professionals. Study findings call for leaders to develop and deploy anticipatory adaptive strategies at the organizational level to mitigate pressures related to system capacity and patient volume and complexity. In turn, anticipatory adaptive strategies can guide efforts by healthcare professionals to manage and adapt their clinical tasks, workload, and demands, ensuring patient safety and workforce resilience at the clinical microsystem level.